Decompressive Craniectomy (DC) - Comparative Study of 30-Day Mortality in Surgeries of Severe Brain Trauma with Subdural Hematoma, with and without DC - Bonadio, Lucas Eduardo; Mello, Luis Renato Garcez; Haas, Leandro Jose; Boer, Vitor Hugo Tamiosso; Bernardes, Celso Itiberê Carvalho; Lara, Danielle De; Cabral, Filipe Laurindo; Peres, Gabriel Hoher; Lindner, Stephanie (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Objective Compare 30 days mortality of patients harboring acute subdural hematomas in two series, one treated only by wide aspiration of hematoma and other with aspiration followed by decompressive craniectomy.Methods Comparing retrospectively two series of ASD with and without DC. Involved 81 TBI patients with acute subdural hematoma and GCS ≤ 8 (Jan 2000 to Nov 2014) arranged into two groups. Group 1 - 58 cases underwent to DC. Group 2 - 23 patients underwent only hematoma aspiration.Results Group 1 showed 44.8% mortality directly due to brain lesion within 30 days. The most frequent associated lesion were contusion in 37.2%. Group 2 the mortality within 30 days was 47.8%. The majority of deaths (82%) resulted from uncontrollable brain swelling, midline shift was present in 94.7% of patients.Conclusion High admission GCS and age less than 50 remain better outcome predictor in 30 days survival for patients undergoing surgery of traumatic ASDH.
Keywords: decompressive craniectomy; acute subdural hematoma; mortality